DNA Barcoding and Phylogenetic Analysis of Commercially Important Groupers (Serranidae) in Raja Ampat using gene marker Cytochrome c Oxidase I (COI) - Ayu, Inna Puspa; Mashar, Ali; Wardiatno, Yusli; Butet, Nurlisa A.; Sani, L. Mukhsin Iqbal; Irianda, Nadya Jeny; Madduppa, Hawis; Gelis, Ester R. E.; Lane, Christopher; Borbee, Erin; Subhan, Beginer (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2024)
Groupers are one of the most important and commercial fishes; many of the species are classified as Life Reef Fish Trade (LRFT). The number of grouper species in these locations may be more diverse than at other sites. Identifying the species number of a grouper is essential for mapping reef fitness. However, morphological identification of groupers is relatively difficult. Molecular methods such as DNA barcoding could be an option and even serve as reliable validation. Therefore, this research was conducted to identify groupers belonging to the Serranidae family. The grouper samples were obtained from the fish market in Waisai, Raja Ampat, Indonesia. The DNA barcoding employed the COI genes to accurately identify groupers. The Qiagen DNeasy 96 tissue extraction kit was used to extract DNA, and Primer Fish F1/R1 was applied. The sequences were analysed using ClustalW in MEGA 7.0 and phylogenetic tree was generated using the NJ (Neighbour Joining) method. Eleven species of groupers belonging to five taxa were discovered in Waisai, Raja Ampat. Anyperodon, Cephalopholis, Epinephelus, Plectropomus, and Variola are the grouper genera. Epinephelus was the predominant genus within the serranidae family, with 51.4% of the total. The International Union for Conservation of Nature's (IUCN) Red List category puts the majority of grouper species in the 'Least Concerned' category. This study confirmed the effectiveness of DNA barcoding for species identification and the value of the COI gene for Grouper's phylogenetic research. The outcome offers information about fisheries resources, which should be helpful in managing fisheries in reef ecosystems.